PELATIHAN MS. Office Word dan Excel BAGI PERANGKAT DESA & MASYARAKAT DESA CIARUTEUN ILIR BOGOR - Max Teja Ajie; Efy Yosrita; Darma Rusjdi; Meilia Nur Indah Susanti; Indrianto Indrianto; Rizqia Cahyaningtyas; Dewi Arianti Wulandari; Herman Bedi Agtriadi (Sekolah Tinggi Teknik - PLN, 2019)
terlampir